2018
DOI: 10.1002/ams2.349
|View full text |Cite
|
Sign up to set email alerts
|

Out‐of‐hospital cardiac arrests in the toilet in Japan: a population‐based descriptive study

Abstract: AimThis study aimed to reveal the characteristics and outcomes of patients with out‐of‐hospital cardiac arrests (OHCAs) occurring in the toilet. These traits provide useful clues for the prevention of OHCAs and the improvement of prehospital care for these patients.MethodsOut‐of‐hospital cardiac arrest data were obtained from the population‐based, Utstein‐style registry in Osaka City, Japan, between 2009 and 2015. This study identified patients with OHCAs that occurred inside the toilet. The primary end‐point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Fisher-Hubbard et al estimated the outpatient incidence of defecation-induced cardiac arrests as 2.3% to 7.4% in patients with cardiovascular disease. Kiyohara et al identified that 4.6% of out-of-hospital cardiac arrest occurred inside the restroom, and the number of patients with the initial shockable rhythm was 5.2%. Based on these studies, it is suggestive that one of the unrecognized causes of sudden cardiac death in patients with heart failure is defecation-induced bradyarrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher-Hubbard et al estimated the outpatient incidence of defecation-induced cardiac arrests as 2.3% to 7.4% in patients with cardiovascular disease. Kiyohara et al identified that 4.6% of out-of-hospital cardiac arrest occurred inside the restroom, and the number of patients with the initial shockable rhythm was 5.2%. Based on these studies, it is suggestive that one of the unrecognized causes of sudden cardiac death in patients with heart failure is defecation-induced bradyarrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported the associations between OHCA-CA and dental caries, [8] seafood consumption, [9] and consumption of carbonated beverages [10] using the All-Japan Utstein Registry. Cold month in the toilet, [11] severe emotional stress, [12,13] climate, [14][15][16] and temperature [17][18][19] have also been reported to be causes of OHCA-CA in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Reports regarding body position at EMS arrival to the arrested patient in the literature are scarce, and this was not the primary consideration of the available publications [11,12,16]. The victim's body position at EMS arrival was not included in the Utstein style reporting of cardiac arrest; therefore, the data were not systematically collected.…”
Section: Discussionmentioning
confidence: 99%
“…However, some information is available from papers regarding the occurrence of cardiac arrest in toilets or circumstances of OHCA recorded on video [16]. Kiyohara et al [12] reported that 4.6% of OHCA in Japan occurred in a toilet. The outcome of these events was poor, mainly because of delayed recognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation